Residential Mobility and Public Policy in OECD Countries - Caldera Sánchez, Aida (OECD Publishing, 2011)
Residential mobility is closely tied to the functioning of housing markets and has important implications for labour mobility and the efficient allocation of resources across the economy. This paper analyses patterns of residential mobility across OECD countries and the role of housing policies in enhancing or hampering residential mobility. Based on cross-sectional household data for 25countries, the results suggest that differences in residential mobility across countries are partially related to differences in public policies. After controlling for household and country- specific characteristics, residential mobility is higher in countries with lower transaction costs, more responsive housing supply, lower rent controls and tenant protection. Residential mobility tends also to be higher in environments with greater access to credit, suggesting that financial deregulation - by lowering borrowing costs and facilitating access to mortgage finance - facilitates mobility. This cross- country evidence is supported by city and state-level evidence for the United States. JEL classification: R23, R31, R21, R38, H20. Keywords: Housing markets, residential mobility, transaction costs, rental market regulations